2017
DOI: 10.1093/mmy/myx105
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the possible regulation of the expression of genes by yapA in Talaromyces marneffei using the qRT- PCR method

Abstract: The pathogenic dimorphic fungus Talaromyces marneffei is known to cause a fatal systemic mycosis in immunocompromised patients, especially in HIV patients in Southeast Asia. The basic leucine-zipper (bZip) transcription factor gene, yapA, has been identified in T. marneffei. A prior study described that yapA was involved in the oxidative and nitrosative stress response in T. marneffei. Interestingly, an essential role of Saccharomyces cerevisiae Yap1p in the oxidative stress response is the activation of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The incidence of invasive fungal infections such as T. marneffei infection has been increasing year by year due to long-term use of immunosuppressive drugs after kidney transplantation as well as the spread of pathogenic microorganisms caused by population movement and the genovariation of the pathogens themselves [ 46 48 ]. Thus, we absolutely cannot ignore the possibility of T. marneffei infection in non-HIV patients in nonendemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of invasive fungal infections such as T. marneffei infection has been increasing year by year due to long-term use of immunosuppressive drugs after kidney transplantation as well as the spread of pathogenic microorganisms caused by population movement and the genovariation of the pathogens themselves [ 46 48 ]. Thus, we absolutely cannot ignore the possibility of T. marneffei infection in non-HIV patients in nonendemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…As an intracellular pathogen, T. marneffei has to alleviate the stress generated in the phagosomal environment. Previous studies reported the role of enzymatic antioxidants in T. marneffei , including superoxide dismutase and catalase-peroxidase; however, only a few studies have characterized the glutathione gene expression profiles 19 , 40 . Indeed, glutathione gene disruption studies have never been performed in this fungal species.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of gst1 + and gst2 + is Pap1-dependent, whereas the induction of gst 3 + is Atf1-dependent 52 . In T. marneffei , the upregulation of TmGcs1 and TmGlr genes in response to oxidative stressors H 2 O 2 , menadione and NaNO 2 are dependent on yapA (Yap1 homolog) in all growth forms (conidia, mold, and yeast) 40 . Besides TmGcs1 and TmGlr genes, other glutathione metabolic genes were not tested in the study by Dankai et al Additionally, while the atfA (SpAtf1 homolog) deletion mutant in T. marneffei shows sensitivity to various oxidative stressors, whether glutathione metabolic gene expression is dependent on aftA was not tested 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 provides information on these 13 candidate targets, including the sequence codes for target search and identification, their functions, alignment parameters (e-value and score), segment similarity, and references to research conducted on these target proteins outside the field of phytopathogenic fungi. The first target listed, Thioredoxin reductase Trr1/Trr2, plays distinct roles in the redox system involving cysteine synthesis and host infection (Dankai, Pongpom, & Vanittanakom, 2018). The second target, Mannose-1-phosphate guanylyltransferase, affects cell growth and morphology by altering cell membrane permeability (Taj et al, 2022).…”
Section: Target Selection From Monosporascus Cannonballus Genomementioning
confidence: 99%